Telaah Kedudukan Organisasi Kemasyarakatan dalam Sistem Ketatanegaraan ditinjau dari Asas Kedaulatan Rakyat - Dzikri Ghufranillah; sri Wahyuni (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2022)
Society organization is a form of public participation to developing democracy as an effort to uphold freedom, equality, togetherness, and honesty. The dynamics of the development of society organization and changes in the government system bring a new paradigm in the governance of society organization in the life of society, nation, and state. So that in order to respond to the development of society organizations, the government imposes a legal system regarding society organization. This research is an effort to describe and examine the problem, first, the relation of the role and function of society organizations and the principle of people's sovereignty. Second, the paradigm of popular sovereignty in the legal system regarding the organization of society. This research is doctrinal legal research or normative legal research with the prescriptive research. Based on the results of the study, the relationship between the role and function of society organizations and the principle of people's sovereignty lies in the participation of the society (public). Likewise, the paradigm of popular sovereignty is implicitly regulated in the legal system in civic organizations through essential principles and procedural principles.